2018
DOI: 10.1080/03009742.2018.1466363
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and response to rituximab in rheumatoid arthritis: results from an international European collaboration

Abstract: Objectives: To investigate whether smoking habits predict response to rituximab (RTX) in rheumatoid arthritis (RA). Method: We included patients from the CERERRA international cohort receiving the first treatment cycle with available smoking status (n = 2481, smokers n = 528, non-current smokers n = 1953) and at least one follow-up visit. Outcome measures were change in Disease Activity Score based on 28-joint count (ΔDAS28) and European League Against Rheumatism (EULAR) good response at 6 months, with non-cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Smokers taking anti-TNF-α have a reduced chance of achieving a moderate response according to the EULAR response criteria compared to non-smokers [132]. Likewise, an observational cohort study evaluated RA patients treated with rituximab: overall results do not support smoking as an important predictor of RTX response in patients with RA [133].…”
Section: Environmental Targetsmentioning
confidence: 94%
“…Smokers taking anti-TNF-α have a reduced chance of achieving a moderate response according to the EULAR response criteria compared to non-smokers [132]. Likewise, an observational cohort study evaluated RA patients treated with rituximab: overall results do not support smoking as an important predictor of RTX response in patients with RA [133].…”
Section: Environmental Targetsmentioning
confidence: 94%
“…New users, sometimes referred to as "biologic-naïve" users, were individuals who had no prescriptions (in pharmacy or medical records) for any of the above medications, or for anakinra or rituximab in the previous year. Rituximab was not included in our analysis due to the uncharacteristically long interval between injections (median time between doses of 7-8 months) (23). New users of anakinra were excluded post hoc when we discovered that they were markedly older and had more comorbidities than patients who started using other bDMARDs.…”
Section: Cohorts Of Rheumatoid Arthritis Patientsmentioning
confidence: 99%
“… 22 Several studies have shown that smokers experience worse outcomes compared to non-smokers to methotrexate, 23 infliximab 19 and combination therapy 18 but, interestingly, not rituximab. 24 The reason for worse clinical outcomes in smokers is not fully understood but smoking is associated with increased levels of pro-inflammatory cytokines such as TNFα 25 that may, in part, explain why TNFi therapy is less effective in smokers compared to non-smokers whilst there appears to be no modifying effect to B-cell depletion therapy.…”
Section: Clinical Factors Predicting Drug Responsementioning
confidence: 99%